P272 Developing a novel medication adherence index to determine reasons for nonadherence in inflammatory bowel disease. (25th January 2019) - Zand, A; Nguyen, A; Stokes, Z; Reynolds, C; Dimitrova, M; Sauk, J; Hommes, D
Abstract: Background: Medication nonadherence is a significant challenge in inflammatory bowel diseases (IBD), and associated with high costs and negative outcomes. The vast majority of studies report nonadherence in IBD in the range of 30–45%. With increased adaptation of electronic health (e-health) technologies, there is a significant opportunity to monitor patient adherence behaviours remotely. However, no tool exists that can both determine adherence levels and quantify patient-specific reasons for nonadherence. We developed a medication adherence index to categorise adherence and assess nonadherence factors in patients with Crohn's disease (CD) or ulcerative colitis (UC) for use in e-health applications. Methods: We performed a cross-sectional study to develop a medication adherence index (MAI) for CD and UC that accurately screens for medication adherence in the IBD population. Our MAI was developed using 27 patient-reported outcomes measures collected from the literature and its predictive performance was compared with the widely used Morisky Medication Adherence Scale-8 (MMAS-8). Data were captured from IBD patients through an electronic questionnaire via email or during clinic visits at the University of California, Los Angeles, Center for IBD from June 2017 to November 2017. Results: In total, 133 patients (65 UC and 68 CD) were included in this study. Our population had 44 (33%) non-adherent and 89 (67%) adherent patients. Our cohort was primarily Caucasian, non-Hispanic, non-smoking and privately insured. No patient characteristics were associated with significant higher nonadherence. Our final 6-item survey for assessing adherence had an area under the curve (AUC), sensitivity, and specificity of, respectively 0.90, 0.87, 0.79, with a score of ≥9 as adherent, and <9 as non-adherent. An additional 4-item survey was developed for nonadherent patients to delineate reasons for their nonadherence. Conclusions: Implementation of this novel tool in e-health applications promising for the monitoring of nonadherence in IBD. Compared with existing scales our new index showed comparable AUC, sensitivity and specificity. There is a potential for more widespread use due to its shorter length and development in a prototypic chronic disease. Additionally, quantifying the reasons for non-adherence can lead to more effective and personalised interventions and education for non-adherent patients. With more tailored solutions for non-adherence, there is a great potential for more patient empowerment, improved clinical outcomes and decreased costs.